Hubungan Self Wound Care dengan Kualitas Hidup pada Pasien Diabetic Foot Ulcer - Nurul Laili; Natasya Adistya Giti As Fitri (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2022)
Diabetic foot ulcer is a chronic complication of Diabetes Mellitus that requires long wound care, high costs and independence which affects the quality of life of the patient. Patient independence in wound care/self wound care requires adequate knowledge, facilities and infrastructure with the aim of reducing costs and anxiety. The aim of the study was to determine the relationship between self wound care and quality of life in diabetic foot ulcer patients. The research design used correlation with a cross sectional approach with a sample of 27 respondents using purposive sampling technique. Data were collected by questionnaire and analyzed using the Rho Spearman Rank test. The results showed that almost half of the respondents(22.22%) had good self-wound care and almost half(22.22%) had a good quality of life. The results of the analysis obtained (ρvalue 0.001<0.05) H1 was accepted, which means that there is a relationship between self wound care and quality of life in diabetic foot ulcer patients with the strength of the relationship being in the moderate category(r=0.433). So that the better the patient's self-wound care, the higher the quality of life will be. It is recommended for patients, families and the community service system to provide motivation, make early detection efforts, educate people with foot diabetic ulcers to improve the degree and quality of patient health. Nursing practice as a solution provided to encourage healthy living behavior through a comprehensive and sustainable clinic or home care(Homecare) to recover, minimize complications, improve health and optimize independence. Keywords: Self Wound Care, Quality of Life, Diabetic Foot Ulcer.